Monitoring Adverse Drug Reactions to Tuberculosis Drugs among Category 1 Patients at Bojonegoro Health Center - Kholillah, Nadhi Fatul; Hutahaen, Titi Agni; Pitaloka, Ria Indah Kusuma (Jurnal Biologi Tropis, 2026)
Tuberculosis caused by Mycobacterium tuberculosis remains a major public health issue in Indonesia. Prolonged use of anti-tuberculosis medications may lead to adverse drug reactions (ADRs). This study aimed to describe the incidence and characteristics of ADRs among Category 1 tuberculosis patients at Bojonegoro Health Center. A descriptive observational study with a retrospective design was conducted during April–May 2026 using medical records and structured interviews. The study sample consisted of 37 patients selected from a population of 40 using the Slovin formula and purposive sampling technique. Data were analyzed descriptively using frequency and percentage distributions, while ADR causality was evaluated using the Naranjo algorithm. The results indicated that ADRs were more frequently observed in female patients, individuals aged 46–55 years, and during the intensive phase of treatment. The most commonly reported ADR was reddish urine discoloration (100.0%), followed by anorexia (67.6%) and nausea (59.5%). Most ADRs were classified as mild to moderate in severity, while decreased vision was reported in 10.8% of patients. Based on the Naranjo scale, 93.4% of ADRs were categorized as probable. Regular monitoring of ADRs is recommended to support early detection and appropriate management during anti-tuberculosis therapy.